Carbon nanotube growth on titanium boride powder by chemical vapor deposition: Influence of nickel catalyst and carbon precursor supply. Issue 8 (1st June 2020) - Lin, Jia; Yang, Yihang; Zhang, Houan; Li, Fenqiang; Yang, Yulin
Abstract: Chemical vapor deposition was employed for the growth of carbon nanotubes (CNTs) on titanium boride (TiB2 ), with nickel (Ni) as the catalyst and methane (CH4 ) as the carbon precursor. The effects of the Ni catalyst and the CH4 supply on the growth of CNTs were evaluated. The crystallinity and microstructure of the CNTs were characterized by XRD, SEM, EDS, TEM, and Raman spectroscopy. Analysis showed that the dispersion and morphology of the carbon products depended on the distribution of the Ni catalyst, and the quantity and length of the grown CNTs were affected by the CH4 gas flow rate. The CNTs grown on the TiB2 substrate with a small amount of impurities and high productivity were well distributed under the following conditions: Ni concentration, 10 wt%; CH4 gas flow rate, 100 mL min −1 ; growth temperature, 850 °C; and duration, 150 min.